Multiple Quality Control Mechanisms in the ER and TGN Determine Subcellular Dynamics and Salt-Stress Tolerance Function of KORRIGAN1 - Nagashima, Yukihiro (Plant Cell, 2020)
Among many glycoproteins within the plant secretory system, KORRIGAN1 (KOR1), a membrane-anchored endo-β-1,4-glucanase involved in cellulose biosynthesis, provides a link between N-glycosylation, cell wall biosynthesis, and abiotic stress tolerance. After insertion into the endoplasmic reticulum, KOR1 cycles between the trans-Golgi network (TGN) and the plasma membrane (PM). From the TGN, the protein is targeted to growing cell plates during cell division. These processes are governed by multiple sequence motifs and also host genotypes. Here, we investigated the interaction and hierarchy of known and newly identified sorting signals in KOR1 and how they affect KOR1 transport at various stages in the secretory pathway. Conventional steady-state localization showed that structurally compromised KOR1 variants were directed to tonoplasts. In addition, a tandem fluorescent timer technology allowed for differential visualization of young versus aged KOR1 proteins, enabling the analysis of single-pass transport through the secretory pathway. Observations suggest the presence of multiple checkpoints/branches during KOR1 trafficking, where the destination is determined based on KOR1’s sequence motifs and folding status. Moreover, growth analyses of dominant PM-confined KOR1-L(48)L(49)→A(48)A(49) variants revealed the importance of active removal of KOR1 from the PM during salt stress, which otherwise interfered with stress acclimation.